Platynosomum fastosum infection in two cats in Belo Horizonte, Minas Gerais State – Brazil. - Vieira , Ana L. S.; Ecco , Roselene; Lima , Walter S.; Guedes, Roberto M. C. (Brazilian Journal of Veterinary Pathology, 2009)
This report describes two cases of cat infection by Platynosomum fastosum in the city of Belo Horizonte, Minas Gerais, Brazil. In case 1, a female shorthair presented at necropsy high infestation by this fluke and had macroscopic and microscopic lesions related to P. fastosum. In case 2, a female shorthair was submitted to necropsy and did not show significant lesions. At Histopathological exam of liver there were a few biliary ducts with flukes with the same characteristics of case 1. In both cases, the diagnosis of P. fastosum was based on morphology of this fluke at histology exam. Additionally , in case 1 a parasitological analysis was performed . To authors knowledge this is the first report of P. fastosum in the city of Belo Horizonte and emphasizes the importance of considering this agent in the differentials related to cholangitis in cats.